2020
DOI: 10.3390/ijms21176028
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Methylome of the Medicinal Plant Catharanthus roseus Unravels the Tissue-Specific Control of the Monoterpene Indole Alkaloid Pathway by DNA Methylation

Abstract: Catharanthus roseus produces a wide spectrum of monoterpene indole alkaloids (MIAs). MIA biosynthesis requires a tightly coordinated pathway involving more than 30 enzymatic steps that are spatio-temporally and environmentally regulated so that some MIAs specifically accumulate in restricted plant parts. The first regulatory layer involves a complex network of transcription factors from the basic Helix Loop Helix (bHLH) or AP2 families. In the present manuscript, we investigated whether an additional epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 91 publications
(129 reference statements)
0
8
0
1
Order By: Relevance
“…As an example, agronomic trait-associated SNPs identified by pan-genome analysis indicated that location and year significantly affected yield-related phenotypes in pigeon pea ( Cajanus cajan ), a plant species with rich vitamin B, protein, ascorbic acid and carotene ( Zhao et al., 2020 ). Developmental methylome of the medicinal plant Cape periwinkle ( Catharanthus roseus ) determined that cellular and physiological functions are likely to be impacted by tissue-specific covariations between context-dependent DNA methylation ( Dugé de Bernonville et al., 2020 ). The cold environment affected ginsenosides accumulation in perennial American ginseng ( Panax quinquefolium ), and a cyclically reversible dynamism between methylation and demethylation of DNA was also reported in response to temperature seasonality ( Hao et al., 2020 ).…”
Section: Advancing Comparative Genomics Genetic Mapping Pan-genome An...mentioning
confidence: 99%
“…As an example, agronomic trait-associated SNPs identified by pan-genome analysis indicated that location and year significantly affected yield-related phenotypes in pigeon pea ( Cajanus cajan ), a plant species with rich vitamin B, protein, ascorbic acid and carotene ( Zhao et al., 2020 ). Developmental methylome of the medicinal plant Cape periwinkle ( Catharanthus roseus ) determined that cellular and physiological functions are likely to be impacted by tissue-specific covariations between context-dependent DNA methylation ( Dugé de Bernonville et al., 2020 ). The cold environment affected ginsenosides accumulation in perennial American ginseng ( Panax quinquefolium ), and a cyclically reversible dynamism between methylation and demethylation of DNA was also reported in response to temperature seasonality ( Hao et al., 2020 ).…”
Section: Advancing Comparative Genomics Genetic Mapping Pan-genome An...mentioning
confidence: 99%
“…Catharanthus roseus produces a wide range of terpenoid indole alkaloids which can be divided into monomeric indole alkaloids (serpentine, strictosidine, ajmalicine, serpentine, catharanthine, vindoline, tabersonine, etc) and dimeric indole alkaloids such as vinblastine and vincristine which are derived from the coupling of catharanthine and vindoline ( Dugé de Bernonville et al, 2020 ). These alkaloids are biosynthesized by the condensation of tryptamine (indole moiety) and secologanin (monoterpenoid) by strictosidine synthase to form strictosidine, a common precursor to all terpenoid indole alkaloids ( Peebles et al, 2011 ).…”
Section: Metabolic Engineering Approachesmentioning
confidence: 99%
“…Some genes encoding key enzymatic steps from the TIA pathway were found to be simultaneously differentially expressed and methylated. The transcription factor ORCA2 displayed hypermethylation in two differentially methylated regions (DMRs) which corresponded to a higher expression in roots vs. mature leaves (Duge de Bernonville et al, 2020).…”
Section: Recent Research Involving Tia Tissue Specificity and Compart...mentioning
confidence: 99%